GIS-material for the archaeological project: East of Trädgårdstorp - Survey preceding laying of sewage pipe between Malmslättsvägen and Rydsvägen - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned trenching for a sewer pipe and a shooting range, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a survey in April 2005. The area is located approximately 100 m east of the Mesolithic settlement RAÄ 126-128 in Kärna parish. No archaeological remains were found and the development works could be conducted without any further archaeological measures being taken.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the survey was to determine whether any archaeological remains were going to be affected by the development works.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför planerad schaktning för spillvattenledning till mottagningsstation och skyttecentrum genomförde Riksantikvarieämbetet UV Öst en arkeologisk utredning i april 2005. Området ligger drygt 100 m öster om den mesolitiska boplatsen RAÄ 126-128, Kärna sn. Inga fornlämningar hittades och de planerade markarbetena kunde genomföras utan ytterligare arkeologisk åtgärd.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med en arkeologisk utredning etapp 2 är att avgöra om fast fornlämning berörs av det planerade exploateringsarbetet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Öster om Trädgårdstorp - Inför anläggande av spillvattenledning mellan Malmslättsvägen och Rydsvägen
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive